Proceedings of the the 15th International Conference on Interaction Design and Children 2016
DOI: 10.1145/2930674.2930714
|View full text |Cite
|
Sign up to set email alerts
|

Connectors in Maker Kits

Abstract: The study of Making to support children's cognitive or social needs is gaining prominence rapidly. However, little research in Making focuses on children's motor skills and abilities, especially at younger ages. Arguing that Making provides greater benefits when introduced at elementary school-aged, this paper contributes to the understanding of how children aged 8 to 11 manipulate connectors, a key component of Maker kits. We present a review of connectors used in prior work, a theoretical foundation based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The ThreadBoard's form has changed with each design iteration, but magnets have remained a constant feature. Magnets provide a connector that makers can immediately understand and enjoy using [2]. Other connectors are employed in e-textile kits: alligator clips and button snaps are two of the most popular [1,2,9,11,17].…”
Section: Features Of a Magnet-based Design 51 Embedded Magnetsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ThreadBoard's form has changed with each design iteration, but magnets have remained a constant feature. Magnets provide a connector that makers can immediately understand and enjoy using [2]. Other connectors are employed in e-textile kits: alligator clips and button snaps are two of the most popular [1,2,9,11,17].…”
Section: Features Of a Magnet-based Design 51 Embedded Magnetsmentioning
confidence: 99%
“…Magnets provide a connector that makers can immediately understand and enjoy using [2]. Other connectors are employed in e-textile kits: alligator clips and button snaps are two of the most popular [1,2,9,11,17]. Alligator clips require more dexterity and physical effort to open and keep open [2].…”
Section: Features Of a Magnet-based Design 51 Embedded Magnetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The types of connections can also affect students' interactions by determining how easily students can make connections to recombine elements. Chu et al found that complex connectors were often misinterpreted by children and their motor skills impacted their ability to physically operate the connectors [11]. Blikstein takes a slightly different approach analyzing the connections through the lens of embedded error correction classifying tools based on their ability to guide students into making connections correctly and thus avoiding errors.…”
Section: Electronic Connectorsmentioning
confidence: 99%